2020
DOI: 10.3389/fneur.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

“It's All Sort of Cool and Interesting…but What Do I Do With It?” A Qualitative Study of Stroke Survivors' Perceptions of Surface Electromyography

Abstract: Background: Stroke is one of the most common neurologic injuries worldwide. Over decades, evidence-based neurorehabilitation research and advancements in wireless, wearable sensor design have supported the deployment of technologies to facilitate recovery after stroke. Surface electromyography (sEMG) is one such technology, however, clinical application remains limited. To understand this translational practice gap and improve clinical uptake, it is essential to include stakeholder voices in an analysis of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Nevertheless, the sample of responders was relatively large (n = 28) and included experts in pediatric rehabilitation: physical therapists, neuro-developmental disorders therapists, and medical doctors ( Figure 4A, left panel). It is also worth noting that many of the barriers for the sEMG use were acknowledged for other populations of patients as well [see, for instance, other articles in this research project: (140)(141)(142)(143)(144)(145)]. Therefore, a general need for this innovative technology suggests that "specific education should be part of the rehabilitation professionals' curriculum" (142).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the sample of responders was relatively large (n = 28) and included experts in pediatric rehabilitation: physical therapists, neuro-developmental disorders therapists, and medical doctors ( Figure 4A, left panel). It is also worth noting that many of the barriers for the sEMG use were acknowledged for other populations of patients as well [see, for instance, other articles in this research project: (140)(141)(142)(143)(144)(145)]. Therefore, a general need for this innovative technology suggests that "specific education should be part of the rehabilitation professionals' curriculum" (142).…”
Section: Discussionmentioning
confidence: 97%
“…The available data were reported and compared with sEMG output. Despite purposefully selecting the Biostamp sensors for their technical features among many other systems previously researched by this study team, there were also limitations in the sEMG sensors themselves, pointing to important needs for future development and research [28,29]. While the design of the sensors was comfortable and unobtrusive to the participant, the size of the sensors may have allowed for cross talk between muscles and decreased the quality of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…Each sensor was 6.6 × 3.4 × 0.3 cm 3 in a housing made of a flexible, low-durometer silicone. These sensors were selected from many research lab-owned systems due to their low profile, flexibility, remote monitoring capabilities, and ability to sanitize in-hospital environments [28,29]. Prior to placement, the skin was prepared by washing with soap and water, and electroconductive gel was applied to each sensor.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, portable systems have been developed for at-home use to improve accessibility and training time with EMG biofeedback [ 13 , 14 ]. However, proper implementation of home-based EMG biofeedback is critical to prevent low participant adherence, avoid high costs, and account for limitations in terms of required physical space, time, and technical literacy [ 14 , 15 , 16 , 17 , 18 ]. Specifically, it has been suggested that the ability to track patient progress in real-time and the continued involvement of a clinician in the intervention are key factors that could improve patient motivation and adherence to at-home rehabilitation programs [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%